Isoforsythiaside confers neuroprotection against Alzheimer’s disease by attenuating ferroptosis and neuroinflammation in vivo and in vitro - Chunyue Wang; Hongbo Jiang; Honghan Liu; Shanshan Chen; Hangyu Guo; Shuoshuo Ma; Weiwei Han; Yu Li; Di Wang (Food Science and Human Wellness)
Ferroptosis and neuroinflammation contribute to the development of Alzheimer's disease (AD). Isoforsythiaside (IFY) is a phenylethanoid glycoside isolated from the dried fruit of Forsythia suspensa (Thunb.) Vahl that has been confirmed to improve the memory and cognitive abilities of APP/PS1 mice in our previous study. The purpose of this study was to explore the anti-ferroptosis and anti-neuroinflammatory properties of IFY-mediated neuroprotection. In APP/PS1 mice, erastin-damaged HT22 cells, and LPS-exposed BV2 cells, the neuroprotective effects against ferroptosis and neuroinflammation were investigated using immunohistochemistry, label-free proteomics, western blot, ELISA, MTT, fluorescence, and TEM. IFY alleviated the expression levels of NO, IL-6, and IL-1β in LPS-exposed BV2 cells and improved the morphology of mitochondria in erastin-damaged HT22 cells. Additionally, IFY upregulated the expression levels of GPX4, FTH, FTL, p-GSK-3β, Nrf2, and NQO1, and downregulated the expression of TFR1, DMT1, p-Fyn, GFAP, p-IKKα+β, p-IκBα, p-NF-κB, and pro-inflammatory factors in the brains of APP/PS1 mice and erastin-damaged HT22 cells. In conclusion, IFY inhibits ferroptosis and neuroinflammation in erastin-damaged HT22 cells and APP/PS1 mice, at least partially by regulating the activation of Nrf2 and NF-κB signaling. IFY may prevent ferroptosis and neuroinflammation in AD and provide a new treatment strategy for AD.